Effects of terrestrial input on macrobenthic food webs of coastal sea are detected by stable isotope analysis in Gaeta Gulf. (5th March 2015) - Careddu, Giulio; Costantini, Maria Letizia; Calizza, Edoardo; Carlino, Pasquale; Bentivoglio, Flavia; Orlandi, Lucia; Rossi, Loreto
Abstract: Stable isotope analysis (SIA) of carbon (δ 13 C) and nitrogen (δ 15 N) was used to analyse the macrobenthic food web dynamics in the Gulf of Gaeta (Tyrrhenian sea, Central Italy) under the influence of discharge from the river Garigliano. Specimens of macrobenthic invertebrates and organic matter (Phytoplankton, detritus and Sediment Organic Matter, SOM) were sampled in eight subtidal sampling sites in the Gulf and subjected to SIA. Bayesian Stable Isotope Mixing Models were used to quantify the proportional contribution of each basal resource to macrobenthic primary consumer diets. The food web topology of each sampling site was also reconstructed and the key food web metrics (connectance, linkage density, mean chain length) were calculated in order to detect potential effects of the river plume at all trophic levels. The δ 13 C signatures of basal resources indicated that bulk organic matter in the Gulf has two main inputs: a) autochthonous, derived from marine primary producers (phytoplankton, seagrass detritus), predominant in the northern part of the Gulf, far from the river mouth, and b) allochthonus, derived from inputs of terrigenous detritus, predominant in the southern part, near the mouth of the river Garigliano. A spatial transition was observed in the main component of primary consumer diets, from phytoplankton (north-western sampling sites) to allochthonous detritus (south-eastern sampling sites), with important influences on the structure of the food webs. Approaching the river mouth we also observed a simplification of network topology in terms of a decrease in the number of species, linkage density and mean food web chain length. Our study provides insight into coastal benthic food web and ecosystem functioning as influenced by river mouths, with particular emphasis on the linkages between pelagic-benthic and terrestrial systems, even on the local scale. Highlights: δ 15 N and δ 13 C values of resources and macrobenthos were assessed in marine habitat. Different basal resource compartments were isotopically characterized. Primary consumers shift in the space their diets. Benthic communities are strongly affected by terrigenous input of Garigliano river. The shift altered the topology of food web within the studied Gaeta Gulf.